2012
DOI: 10.1111/anec.12007
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Electrocardiographic Estimation of Left Ventricular Hypertrophy in Dialysis Patients

Abstract: ECG scoring of LVH can be predictive of cardiovascular mortality. The Novacode method, based on repolarization abnormalities, is a better predictor than standard ECG techniques that are based on voltage criteria. Novacode LVH estimation at dialysis initiation may prove to be a noninvasive and cost-effective bedside tool for cardiovascular risk stratification in patients receiving dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…Using a different statistical approach, we defined a new cut-off for RFO – 17.4% and showed that this value performs better than the previous one in survival analyses. Most importantly, this new threshold remains independently associated with mortality, even after adjustment for different baseline echocardiographic parameters–essential confounders for mortality risk predictions, as shown repeatedly in previous studies [ 17 – 21 ]. Thus, besides confirming data from a single previous cohort, we now robustly bring proof that bioimpedance parameters are significant predictors for outcomes, even when adjustments are made for cardiovascular comorbidities or for well-recognized predictors such as LVMI or cardiac function.…”
Section: Discussionsupporting
confidence: 71%
“…Using a different statistical approach, we defined a new cut-off for RFO – 17.4% and showed that this value performs better than the previous one in survival analyses. Most importantly, this new threshold remains independently associated with mortality, even after adjustment for different baseline echocardiographic parameters–essential confounders for mortality risk predictions, as shown repeatedly in previous studies [ 17 – 21 ]. Thus, besides confirming data from a single previous cohort, we now robustly bring proof that bioimpedance parameters are significant predictors for outcomes, even when adjustments are made for cardiovascular comorbidities or for well-recognized predictors such as LVMI or cardiac function.…”
Section: Discussionsupporting
confidence: 71%
“…The Peguero-Lo Presti and Cornell voltage therefore provide valuable independent information for risk prediction in these patients. Hence, in agreement with previous reports, the Peguero-Lo Presti voltage might be preferable for risk prediction in this population [11,29,31]. As expected, and comparable to previous studies, not only did the Sokolow-Lyon voltage identify fewer positive patients, but it was also not predictive of mortality [29,35].…”
Section: Discussionsupporting
confidence: 92%
“…Cardiac function was also improved in the aldosterone antagonists group. Left ventricular mass (LVM) is a powerful independent predictor of cardiovascular morbidity and mortality [ 25 ]. Increased LVM has also been associated with coronary artery disease, all-cause mortality, and sudden death [ 26 ].…”
Section: Discussionmentioning
confidence: 99%